PAYMENT FOR ENVIRONMENTAL SERVICES APPROACH TO REDUCE FLOOD IN CILIWUNG WATERSHED - Tri Ratna Saridewi; Setia Hadi; Akhmad Fauzi; I Wayan Rusastra (SEAMEO BIOTROP, 2017)
Spatial planning has already been stipulated in Ciliwung Watershed, but its implementation is often not in line with the rapid development activities. To fulfill space demand, agricultural and forest areas are converted into open or built-up areas because the economic appreciation of forest and agricultural land is lower than that of open or built-up areas. Payment for Environmental Services (PES) is a tool designed to overcome environmental mismanagement, which is beneficial for the lives of rural communities. PES should be considered in the formulation of spatial planning. This study was aimed to develop optimum land use pattern in reducing flood in Ciliwung Watershed, using PES approach. This study used a dynamic system approach, consisting of submodels for land use pattern change, runoff, value of farmland, upstream subsidy policy, population dynamics, and environmental services. The results showed that the PES policy should be able to maintain the existence of paddy fields and dryland farming areas and to reduce runoff if it is implemented in the form of guaranteed access to the market, and held in conjunction with efforts to prevent land conversion and to implement reforestation policies. The optimum land use pattern under this condition shall be reached in 2023, which consisted of 0.82% water bodies, 10.74% forest areas, 70.34% built-up areas, 8.16% dryland farming areas, 4.97% grassland areas, 2.39% paddy field areas, and 2.58% open areas. This land use pattern can reduce runoff in Ciliwung River from 972.04 to 850 cm, and this level is considered to be flood-free. Communities living in the upstream areas are the most effective managers of the watershed.